Geochemistry and mineralogy of the Oligo-Miocene sediments of the Valley of Lakes, Mongolia - Richoz, Sylvain (Paleobiodivers Paleoenviron, 2017)
The Valley of Lakes is approximately a 500-km elongate depression in Central Mongolia, where Eocene to Miocene continental sediments are long known for their outstanding fossil richness. The palaeontological record of this region is an exceptional witness for the evolution of mammalian communities during the Cenozoic global cooling and regional aridification. In order to precisely elucidate the climatic evolution of the region, we studied the mostly siliciclastic sediments with several levels of paleosols for their sedimentology, mineralogy, major and trace element composition and δ(13)C and δ(18)O composition. The obtained results show that temperate hydrothermal fluids induced a strong illitization of the fluvial and lacustrine sediments. This finding contradicts the current conceptual view that the fine fraction of the sediments is of aeolian origin. Moreover, the diagenetic growth of illite resulted in a strong overprinting of the sediments and, subsequently, largely disturbed the pristine mineralogical and geochemical composition of the sediments that could have carried any palaeo-climatic information. An exception is the δ(13)C (and δ(18)O) isotope values of authigenic carbonate found in calcrete horizons that still record the ambient climatic conditions prevailing during paleosol formation. Our novel δ(13)C and δ(18)O record suggests an early Oligocene aridification in Central Asia at ∼31 Ma, whereas the Oligocene glacial maximum shows no increase in aridification. A second, regional-scale aridification occurs at ~25 Ma and corresponds to a late Oligocene marked mammalian turnover in the Valley of Lakes sediments.